Investigations of a printed circuit heat exchanger for supercritical CO2 and water - Song, Hoseok (Kansas State University, 2007)
In the STAR-LM (Secure Transportable Autonomous Reactor-Liquid Metal) reactor concept developed at Argonne National Laboratory (ANL), a supercritical CO2 (S-CO2) Brayton cycle is used as the power conversion system because it features advantages such as a higher efficiency due to less compressive work, and competitive cost due to a reduced complexity and size. From the components of the cycle, high performance of both the recuperator and precooler has a large influence on the overall cycle efficiency and plant economy. One attractive option for optimizing the performance of the cycle is to use an high efficiency heat exchanger such as the Printed Circuit Heat Exchanger (PCHE) manufactured by Heatric. The PCHE is a compact heat exchanger with high effectiveness, wide operating range, enhanced safety, and low cost. PCHEs are used in various industrial applications, but are relatively new to the nuclear industry. In this study, performance testing of a PCHE using supercritical CO2 and water as heat transfer media were performed at ANL. The heat transfer characteristics of the PCHE under operating conditions of the STAR_LM precooler were investigated. The S-CO2 , defined the “hot-side”, had its outlet condition near the pseudocritical point at 7.5MPa (~31-32 C). We found that of all the thermophysical properties undergoing rapid change near the critical point, heat transfer for S-CO2 is strongly correlated with the specific heat of CO2. Additional experiments performed with different bulk temperatures and pressures on the hot side also supported this conclusion. We proposed plotting the heat transfer results, (Nu2 + Pr2/3) versus (RePr4/3), based on an order-of-magnitude analysis, to reveal the close proximity of the outlet to pseudocritical conditions. In order to check the experimental results, a nodal model of a segmented PCHE using a traditional log-mean temperature difference method was developed. This approach provided the temperature distribution along the heat exchanger. Additionally a CFD simulation (FLUENT) of a 4-layer, zig-zag channeled PCHE was developed. Comparison of the simulation and LMTD nodal model revealed that indeed specific heat strongly influenced the heat transfer.
Keywords: Compact heat exchanger; Supercritical; Engineering, Mechanical (0548)